Readiness of the Science Education Study Program in the Implementation of the ‘Merdeka Belajar - Kampus Merdeka’ (MBKM) Curriculum - Zakiyyah Zakiyyah; Mutiara Dwi Cahyani; Nurwanti Fatnah (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2021)
The purpose of this research is the readiness of the science education study program to implement the MBKM curriculum, which is explained through the characteristics of cooperation, lecturer competence, student perception and participation, and analysis of stakeholder needs. The research method uses case study qualitative analysis, and the subjects are teachers, students, and stakeholders in the science education study program. One of the results obtained is the characteristics of the cooperation carried out by the achievement of the graduates. The competencies possessed by lecturers as facilitators in the implementation of MBKM. There is a biased understanding of students' perceptions and involvement in the implementation of MBKM. The stakeholders involved in the preparation of this curriculum have conformity with the needs of the curriculum structure. Furthermore, these results can be used as the basis for the readiness of the Science Study Program in implementing MBKM.